Improving EFL Writing Performance through Reading Short Stories - ELKEBAILI, Farid (My University, 2022)
Both reading and writing play key roles in EFL teaching and learning. They are reported to increase pupils’ chances for personal, educational successes, and later for employable requirements. Providing that writing is a complex cognitive activity that requires students to control its variables, reading is believed to be the key to upgrade this control, and thus, enable students to promote their writing proficiency. This research work aims at investigating the direct outcomes of short story reading on pupils’ writing abilities. The study was conducted at BEKKADA Belmehel Secondary School in Mazouna involving a sample group of 20 first year scientific pupils. The study involves a sequential explanatory mixed method design; pupils’ pre- and post-tests to check their writing normality, a pupils’ questionnaire to determine their attitudes towards this skill, and a teachers’ interview to highlight their perceptions towards reading-writing integration and short story implications on the enhancement of writing performance, in addition to a four-week short story reading programme as an intervention before having the sample post-tested. The data of this empirical study revealed that first-year secondary school pupils had weaknesses in writing, and faced difficulties in processing this skill. The data obtained in the pre-test and the post-test have been assessed with four criteria represented in form and content; and in the light of the results obtained, the correlation of both scores has been examined. The data analysis indicated that the intervention had little impact on the sample’s writing performances being disclosed through the low rates of improvement demonstrated in the sample’s products. Likewise, much of the language used in their products was mostly non-academic. This was explained by the effect of the digital mediated language they are exposed to in their daily life. The study, therefore, provided recommendations urging EFL teachers to maintain the use of short story through digital strategies in order to boost pupils’ writing skills.
A Case Study of First-Year Scientific Class at BEKKADA Belmhel Secondary School – Mazouna – Relizane
Keywords: EFL classroom; reading; writing; short stories; secondary school pupils; digital